2020
DOI: 10.1016/j.scib.2020.05.013
|View full text |Cite
|
Sign up to set email alerts
|

A selective control of volatile and non-volatile superconductivity in an insulating copper oxide via ionic liquid gating

Abstract: Electric-field control of non-volatile magnetization switching without external-magnetic-field bias in CoFeB/(011)-PMN-0.3PT heterostructures Europhysics letters 109, 17008 (2015); Simulations of single event effects on the ferroelectric capacitor-based non-volatile SRAM design SCIENCE CHINA Information Sciences 64, 149401 (2021); Simulation of Titan's atmospheric photochemistry-Formation of non-volatile residue from polar nitrile ices Astronomy & Astrophysics 578, A111 (2015); Non-volatile memory based on ato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 53 publications
(110 reference statements)
1
2
0
2
Order By: Relevance
“…Similar observation was obtained in the EDLT of NdBa 2 Cu 3 O 7 . On the electron-doped side, a very recent study on Pr 2 CuO 4 showed that the gating mechanism can indeed cross from a purely electron-doping scheme in the positive gating ,, to the filling of oxygen vacancies in the negative gating . In general, these studies focus exclusively on oxygen ions/vacancies, leaving the possible involvement of protons an open issue.…”
supporting
confidence: 71%
See 1 more Smart Citation
“…Similar observation was obtained in the EDLT of NdBa 2 Cu 3 O 7 . On the electron-doped side, a very recent study on Pr 2 CuO 4 showed that the gating mechanism can indeed cross from a purely electron-doping scheme in the positive gating ,, to the filling of oxygen vacancies in the negative gating . In general, these studies focus exclusively on oxygen ions/vacancies, leaving the possible involvement of protons an open issue.…”
supporting
confidence: 71%
“…By going to more negative voltages (sequence >17 in Figure d), superconductivity gets suppressed again. We surmise that oxygen ions, produced previously during water electrolysis, can be pushed into the sample. , They fill the oxygen vacancies and reduce conduction carriers, which tends to drive the sample to an insulator.…”
mentioning
confidence: 94%
“…Möckli和Khodas [66] 认为面内平行磁场将s波 转变为同位旋的f 波, 最终得到s+if非常规超导. Liu [67] , Nakamura和Yanase [68] [76,77] , YBCO [78,79] , La 2 -CuO 4+δ [80] , Pr 2 CuO 4+δ [81] 和NdBaCu 3 O 7 [82] , 以及电子掺 杂的Pr 2−x Ce x CuO 4 [83,84] 和La 2−x Ce x CuO 4 [85,86] . 高T c 的超导态.…”
Section: 供了便利 相比单层样品中能量最低谷在K点 多层样unclassified
“…Shimizu等人 [101] [102] . Wei等人 [81] 发现在 Pr 2 CuO 4+δ 的调控中, 正栅压下H + 进入样品引入电子掺 杂, 而负栅压时CuO面上的氧缺陷被修复. Cui等人 [103] 则用核磁共振(NMR)实验证实了H + 注入在系列铁基超 导体(11和122体系)的调控中发挥了重要的作用.…”
Section: 学腐蚀导致的临界厚度加上静电场调控的结果 并在unclassified
“…However, ionic liquids are not suitable for industrial applications since they are not easily separated and recovered in reaction systems. 15 Thus it is significant to find suitable carriers to prepare heterogeneous catalysts with strong catalytic activity, high stability and easy recyclability in transesterification between glycerol and DMC to prepare GC. 16,17…”
Section: Introductionmentioning
confidence: 99%